Respuesta :

MAMJ
The work out the length of the missing side you need to use Pythagoras' theorem which states that the sum of the squares of the two sides, in this case x and 60, is equal to the sum of the square of the hypotenuse. This can be formulated as [tex] a^{2} +b^{2}=c^{2}[/tex]. In this case x can replace a or b (I've replaced a).
[tex] x^{2} +b^{2}=c^{2}[/tex] 
To solve for x rearrange the equation by subtracting [tex] b^{2}[/tex] from both sides:
[tex] c^{2} -b^{2}=x^{2}[/tex]
Substitute the numbers in:
[tex] x^{2} = 61^{2} -60^{2}[/tex] 
                 = 3721-3600
                 = 121
Take the square root of 121 to find x:
x =[tex] \sqrt{121} [/tex]
   = 11cm 

Answer:

11

Explanation:

Using the Pythagorean Theorem,

a² + b² = c² is the same as c² - b² = a²

c = 61

61^2 =  61 X 61 = 3,721  

b = 60

60^2 = 60 X 60 =  3,600  

Next, we subtract:

3,721 - 3,600 = 121  

√121 = 11

(x = 11 cm)

so 11 is your answer